Organizational structure and convergent change (2021)
Purpose By integrating the structural contingency and the organizational adaptation theories, this study analyzes the impact of the main variables of organizational structure on convergent change. The authors also examine whether some contingency variables, such as the firm's size, age and sector, may help to explain differences in the relationship between organizational structure and convergent change. Design/methodology/approach This work was carried out through an explanatory and cross-sectional study. The hypotheses were tested through a multiple regression analysis. Findings This paper demonstrates that, in Bogota's SMEs, modifications in differentiation and formalization explain convergent change, and that centralization does not affect it. Furthermore, the authors find that the company's size explains these relationships, and that age and sector do not influence them. Practical implications The authors provide useful information in this work to guide managers and professionals on the implications of organizational structure and convergent change, more specifically on decisions regarding hierarchical arrangement, job division and processes redefinition. Originality/value This work provides empirical evidence with original data for a better understanding of the reality of Colombian SMEs in the Latin American context.